Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan, Leverage, Struktur Modal terhadap Kinerja Keuangan : Studi Empiris pada Perusahaan Sub Sektor Insurance Tahun 2019 -2023 yang Terdaftar pada Bursa Efek Indonesia - Aghnia Gita Apralia; Rinny Meidiyustiani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze and determine how managerial ownership, firm size, leverage, and capital structure affect financial performance in insurance companies listed on the Indonesia Stock Exchange from 2019 to 2022. The study focused on 15 companies that met the sample criteria and were deemed representative of the Indonesian insurance industry during that period. The data used in this study were sourced from officially published company financial reports. Furthermore, the data was processed using Microsoft Excel 2018 and SPSS version 25 software to ensure accurate analysis results. The analysis method used was multiple linear regression, as it is considered appropriate for testing the influence of more than one independent variable on the dependent variable. This approach allows the researchers to identify whether each independent variable has a significant effect on financial performance when tested simultaneously. The results showed consistent findings across all variables. First, managerial ownership has a positive and significant effect on financial performance. This indicates that the higher the managerial ownership, the better the alignment of interests between managers and shareholders, leading to improved financial outcomes. Second, company size also has a positive and significant effect on financial performance, meaning the larger the company, the better the performance. Furthermore, leverage has been shown to have a positive and significant effect on financial performance. This suggests that optimal use of debt can enhance company performance by providing additional resources for growth. Finally, capital structure also has a positive and significant effect on financial performance, indicating that the right combination of debt and equity can increase company value. Overall, the findings highlight the importance of financial and managerial decisions in shaping the performance of insurance companies in Indonesia during the observed period.